IMPLEMENTASI PERATURAN GUBERNUR NO. 24 TAHUN 2017 TENTANG PEMUNGUTAN PAJAK BAHAN BAKAR KENDARAAN BERMOTOR PADA BADAN PENDAPATAN DAERAH PROVINSI LAMPUNG - ida farida; Seprina Harisman (e-JKPP, 2020)
The problems in this study are: (1) How is the Implementation of Governor Regulation Number 24 of 2017 concerning Tax Collection of Motorized Vehicle Fuel in the Regional Revenue Agency of Lampung Province. (2) What aspects are hampering the Implementation of Governor Regulation Number 24 of 2017 concerning Collection of Motor Vehicle Fuel Taxes in the Revenue Agency of Lampung ProvinceThe research method used in this research is to use qualitative research types with descriptive analysis methods. The use of this method is to study and describe qualitatively, how the Implementation of the Governor Regulation Number 24 of 2017 concerning Collection of Motor Vehicle Fuel Taxes in the Revenue Agency of Lampung Province. All data obtained directly from informants in the field using interview and observation techniques, according to the research objectives to be achieved.The results showed that the Implementation of the Governor Regulation Number 24 of 2017 concerning Motor Vehicle Fuel Tax Collection has been carried out. This is consistent with the results of research showing that the implementation of the program is still entirely sourced from the top or top down, both from the program activities and the funding has been carried out but not yet optimal. The implementer cannot innovate because it is clear that the program must be implemented, although sometimes it is not suitable with local conditions. Then the taxpayers feel less socialized by the Governor Regulation Number 24 of 2017 concerning Collection of Motorized Vehicle Fuel Taxes, because not many taxpayers who have been using taxable facilities know about it, so the government sometimes uses its rights suddenly without being socialized first first.Aspects that hinder the implementation of Governor Regulation Number 24 of 2017 concerning Tax Collection of Motorized Vehicle Fuel at the Regional Revenue Agency of Lampung Province, namely (1) Awareness of taxpayers in paying taxes on time, has not been implemented in accordance with the specified time so that tax arrears occur, (2) The role of the implementing staff of Motor Vehicle Fuel Tax Collection which is not yet optimal in socializing the tax payment system, so that the implementer has not fully been able to carry out his duties optimally.